World currencies as foundations of capitalism in the process of globalisation (Economic and Political Thought, 2015)
The aim of the article is to identify the stages of development of theAmerican dollar and three currencies orbiting it (the euro, pound sterling andSwiss frank) with the use of econometric methods and to make comparisonsin order to highlight the mechanisms of long-term changes in the valueof world money. The author analysed not only the dynamics of currencyexchange rates in time but also reason-effect relationship of the changes.This was used to develop the dollar’s value forecast until 2024 and the euro’svalue one until 2020.